Kajian Arsitektur Biophilic pada Arsitektur Tradisional Bali sebagai Pendukung Ekowisata di Bali (Studi Kasus: Rumah Adat Bali) - Pande Putu Dwi Novigga Artha; Nyoman Warnata; Anasta Putri (Universitas Sebelas Maret Surakarta, 2022)
The development of the times indirectly affects human needs which have an impact on all aspects of human life, psychology, lifestyle to architecture. There are several rules of Traditional Balinese Architecture that contrast or are not suitable when combined with modern architecture that is in demand by today's society. However, if ecotourism buildings in Bali follow the architectural trend in the world, it will violate the Bali Regional Regulation and Bali will lose its architectural identity. There is a gap between traditional Balinese architecture that must be applied with modern architecture which is the current trend. Biophilic Architecture is building's connection to the environment will affect the health of the community both physically and psychologically. In general, the Biophilic approach and Traditional Balinese Architecture are both environmentally based. Therefore, Biophilic Architecture can be a bridge between Traditional and Modern Architecture. Using comparative quantitative research methods with biophilic as an indicator of assessing traditional Balinese architecture, the results of modern architecture guidelines that have environmental-based traditional rules will be obtained. This research is expected to be a guide or reference in designing ecotourism buildings that are modern but still strong in their traditional Balinese identity.